2010
DOI: 10.5194/nhess-10-7-2010
|View full text |Cite
|
Sign up to set email alerts
|

Electron and ion density variations before strong earthquakes (<i>M</i>>6.0) using DEMETER and GPS data

Abstract: Abstract. Using IAP (plasma analyzer) and ISL (Langmuir probe) experiments onboard DEMETER (Detection of Electromagnetic Emissions Transmitted from Earthquake Regions) satellite and GPS (Global Positioning System) measurements, we have statistically analyzed the variations of the electron and ion densities to search for disturbances in the vicinity of four large earthquakes prior to events. The indices D st and K p were used to distinguish pre-earthquake anomalies from the other anomalies related to the geomag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 25 publications
8
88
0
2
Order By: Relevance
“…The strong seismotelluric current is thought to run mainly along the Longmenshan fault and electromagnetic oscillations, induced by the current and predominated by ULF frequency band, propagate up to the ionosphere and give rise to perturbations of ionospheric parameters. Some of these parameters have been investigated, such as GPS TEC and f0F2 (Yu et al, 2009;Xu et al, 2010;Akhoondzadeh et al, 2010), DEMETER satellite O+ density (Zhang et al, 2009b), electron density and electron temperature (Zeng et al, 2009), etc. Fortunately, all of these study results present a climax on 9 May 2008 and this indicates a LAIC or interaction aroused by these electromagnetic signals prior to the Wenchuan event.…”
Section: Discussionmentioning
confidence: 99%
“…The strong seismotelluric current is thought to run mainly along the Longmenshan fault and electromagnetic oscillations, induced by the current and predominated by ULF frequency band, propagate up to the ionosphere and give rise to perturbations of ionospheric parameters. Some of these parameters have been investigated, such as GPS TEC and f0F2 (Yu et al, 2009;Xu et al, 2010;Akhoondzadeh et al, 2010), DEMETER satellite O+ density (Zhang et al, 2009b), electron density and electron temperature (Zeng et al, 2009), etc. Fortunately, all of these study results present a climax on 9 May 2008 and this indicates a LAIC or interaction aroused by these electromagnetic signals prior to the Wenchuan event.…”
Section: Discussionmentioning
confidence: 99%
“…The geomagnetic conditions are quiet on these dates (Kp<2.5 and Dst>−20 (nT)). A dominant anomaly was observed in electron density parameter measured by ISL (Langmuir probe) sensor, 5 days before the earthquake at nighttime (Akhoondzadeh et al, 2010). Using the analysis of the DEMETER data, Molchanov et al (2006) reported a drop of the VLF signals radiated by ground transmitters prior to large earthquakes.…”
Section: C) Intensity Of Ice Vlf Spectrogram Of the E12 Electric Compmentioning
confidence: 99%
“…The time series of the electron temperature variations, measured by the ISL experiment, display a sudden increase in electron temperature, 2 days before the earthquake, at ∼22:30 LT (Akhoondzadeh et al, 2010).…”
Section: Observed Anomalies Using Hf Data Of Ice Experiments Onboard Dmentioning
confidence: 99%
See 2 more Smart Citations